(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Irawati W, Riak S, Sopiah N, Sulistia S. 2017. Heavy metal tolerance in indigenous bacteria isolated from the industrial sewage in Kemisan River, Tangerang, Banten, Indonesia. Biodiversitas 18: 1481-1486. The bacterial study is a part of human calling in preserving the earth. Many indigenous bacteria isolated from heavy metal contaminated sites had resistance to heavy metal toxicity and could be used for heavy metal removal. The aims of this study were to isolate heavy metal-tolerant indigenous bacteria from the industrial sewage of Kemisan River in Tangerang, Banten, Indonesia. The potency of bacterial isolates to remove heavy metals was also determined. The heavy-metal tolerance was determined by measuring the minimum inhibitory concentration. The potency of bacterial isolate for removing heavy metals from the medium was determined by an atomic absorption spectrophotometer. The results showed that there were eight heavy metal-resistant bacteria isolated from Kemisan River with minimum inhibitory concentration ranging from 7 mM to 11 mM. Isolate PbSI1 was the highest lead tolerant bacteria, and also tolerant to copper and zinc. The isolate was able to remove 91.25% lead, 73.38% zinc, and 98.57% copper from medium supplemented with the mixture of these heavy metals. The addition of 9 mM of lead in the medium affected the morphological appearance of isolate colonies i.e PbSI1 and PbSI3 to become darker which might occur due to the survival mechanism of bacteria by absorbing the lead inside the cells. The finding of this study indicated that isolate PbSI1 was a promising bacterium, which could be further developed for heavy metal removal.